Owner's Perception, Accounting Knowledge, and Education Level on the Use of Accounting Information - Irmawati; Sahabuddin; Ilham Z Salle (Value Relevance: Jurnal Akuntansi, 2024)
This research aims to determine the influence of the variables of owner perception, accounting knowledge, and level of education on the use of accounting information. The population in this research is SMEs in Jayapura City. Sampling in this study used the Random Sampling technique, research data was obtained using a research instrument in the form of a questionnaire which was distributed directly to respondents containing 18 question items measured using a Likert scale. The data analysis method in this research uses multiple linear regression. The research results show that the owner's perception, accounting knowledge, and level of education have a positive and significant effect on the use of accounting information. The contribution from the results of this research provides information to SMEs about the importance of using accounting information to make it easier for SMEs to manage their businesses and also make decisions.